Turning Aliens into Socialists: Localization of a UFO Mythical Complex in Sweden - Moberg, Jessica (International journal for the study of new religions, 2010)
Immediately after the Second World War Sweden was struck by a wave of sightings of strange flying objects. In some cases these mass sightings resulted in panic, particularly after authorities failed to identify them. Decades later, these phenomena were interpreted by two members of the Swedish UFO movement, Erland Sandqvist and Gösta Rehn, as alien spaceships, or UFOs. Rehn argued that ‘[t]here is nothing so dramatic in the Swedish history of UFOs as this invasion of alien fly-things’ (Rehn 1969: 50). In this article the interpretation of such sightings proposed by these authors, namely that we are visited by extraterrestrials from outer space, is approached from the perspective of myth theory. According to this mythical theme, not only are we are not alone in the universe, but also the history of humankind has been shaped by encounters with more highly-evolved alien beings. In their modern day form, these kinds of ideas about aliens and UFOs originated in the United States. The reasoning of Sandqvist and Rehn exemplifies the localization process that took place as members of the Swedish UFO movement began to produce their own narratives about aliens and UFOs. The question I will address is: in what ways do these stories change in new contexts? Texts produced by the Swedish UFO movement are analyzed as a case study of this process.